2008
DOI: 10.2527/jas.2007-0411
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding sericea lespedeza hay on growth rate of goats naturally infected with gastrointestinal nematodes1

Abstract: Goat production is increasing in the United States due to high ethnic demand, but infection with gastrointestinal nematode (GIN) parasites is a major constraint to the industry. Increasing GIN resistance to chemical anthelmintics worldwide has led to the development of alternative control strategies, including use of forages containing condensed tannins (CT). An experiment was designed using infected and dewormed male kids (Kiko x Spanish, 6 mo old, 18.9 +/- 3.25 kg) fed diets containing 25% concentrate and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 34 publications
(46 reference statements)
5
45
0
Order By: Relevance
“…The present findings are in agreement with the previous report (Sokerya and Preston 2003), who reported that dietary supplementation of CT may be used as an alternative parasite management strategy. Moore et al (2008) reported that feeding SL hay can reduce FEC and increase performance of goats compared with Bermuda grass (BG) hay. The effect of reduced GIN infection levels in kids fed SL hay confirms the reports with sheep and goats fed this forage in different dried forms (Shaik et al 2006;Lange et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The present findings are in agreement with the previous report (Sokerya and Preston 2003), who reported that dietary supplementation of CT may be used as an alternative parasite management strategy. Moore et al (2008) reported that feeding SL hay can reduce FEC and increase performance of goats compared with Bermuda grass (BG) hay. The effect of reduced GIN infection levels in kids fed SL hay confirms the reports with sheep and goats fed this forage in different dried forms (Shaik et al 2006;Lange et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the number of reports showing the anthelmintic effect of CT rich plants on goats, naturally and experimentally infected by GI nematodes, has increased. As previously described for sheep, a reduction in egg excretion and in fecundity of the female worms have been reported in goats fed bioactive plants such as sainfoin (Onobrychis viciifolia, Hoste et al, 2005a;Paolini et al, 2003bPaolini et al, , 2005b, sericea lespedeza (Lespedeza cuneata, Min et al, 2004Min et al, , 2005Moore et al, 2008;Shaik et al, 2006;Terrill et al, 2007Terrill et al, , 2009, sulla (Hedysarum coronarium, Pomroy and Adlington, 2006), and Viscum verrocosum (Madibela and Jansen, 2003). These results were obtained in trials where goats were naturally or experimentally infected by GI nematodes, but under controlled conditions.…”
Section: Promising Use Of Plants As Nutraceuticals In Goatsmentioning
confidence: 66%
“…It also has been reported that tannin-rich plants do not have an effect on LW (Kahiya et al, 2003;Osoro et al, 2007), blood parameters (Kahiya et al, 2003;Terrill et al, 2007;Terrill et al, 2009;Whitley et al, 2009), and milk production (Hoste et al, 2005a) and milk concentrations of fat, protein or lactose (Min et al, 2005). However, these finding are not consistent with the results of other studies such as Min et al, (2005), Shaik et al, (2006), Moore et al, (2008), and Osoro et al, (2009). The deviations between studies in goats may come from differences in the concentration and the structure of the condensed tannins present in the different plant species, the structure and chemical characteristics of condensed tannins, parasite species, developmental stages of parasites, quality of feed exposure to tannins (Brunet et al, 2008), environmental conditions and host species Alonso-Díaz et al, 2010).…”
Section: Effect Of Tanninsmentioning
confidence: 67%
“…Signs of copper toxicity are not apparent in growing goats supplemented with 100 mg/day of copper or less (NRC 2007). In comparing sheep and goats with regard to their susceptibility to copper toxicity, goats are less susceptible than sheep (Burke and Miller 2008). This difference is likely to be related to their ability to absorb, store copper in the liver, and then clear it from their body .…”
Section: Effect Of Copper Oxide Wire Particlesmentioning
confidence: 99%
See 1 more Smart Citation